CANARIES IN A COAL MINE: RULE OF LAW DEFICIENCIES AND MUTUAL TRUST - Bárd, Petra (Pravni zapisi, 2021)
The value decline in the EU has manyfold consequences. It jeopardizes the very essence of Europe as a community of values. At the same time it endangers legal principles, such as mutual recognition, which is based on mutual trust presuming that all Member States are based on the rule of law and protect fundamental rights. Once trust is rebutted, Member States’ judicial authorities will refuse to cooperate and recognise each other’s judgments in order not to become complicit in individual rights violations and not to contradict the European Convention for the Protection of Human Rights and Fundamental Freedoms. This paper argues that EU law must allow for such considerations and suspend mutual recognition-based laws not only on a case-by-case basis, as it happens today in practice, but in general with regard to Member States undergoing rule of law decline, in order to uphold the EU’s fundamental rights culture, ad EU law’s equivalency with the Convention’s human rights regime.